An assessment towards the acceptance of wearable technology to consumers in Turkey: the application to smart bra and t-shirt products - TURHAN, GÜLDEN (TAYLOR & FRANCIS LTD, 2013)
The study attempts to predict the dynamics that play a role in the process through which consumers accept wearable technology. A research model, in the form of a structural diagram, is proposed in search of the acceptance or buying intention of wearable technology via subjective norms, perceived usefulness, attitude towards the behaviour, perceived behavioural control and the related beliefs. In the study applied to smart bra and t-shirt products, the results show that subjective norms and attitudes towards behaviour are found significant in direct influence to buying intention, but perceived usefulness is not directly related to it. Perceived usefulness and behavioural control are found significant to indirect influence in buying intention through their effects on attitude. In addition, perceived behavioural control is directly related to attitude only for smart bras. In both the products, subjective norms, perceived usefulness, attitude and perceived behavioural control appear to be explained by a set of salient beliefs.
Keywords: wearable technology; acceptance; attitude; usefulness; subjective norms; perceived control; SELF-EFFICACY; PLANNED BEHAVIOR